Availability of ultra-processed food associated with health outcomes: a systematic review. (30th September 2020) - Pereira de Araújo, T; Moraes, M; Magalhães, V; Afonso, C; Rodrigues, S
Abstract: Background: Ultra-processed food (UPF) consumption increases worldwide, which can be harm to population's health. To establish associations between UPF and health outcomes, food consumption can be assessed individually or by using availability data, such as purchase lists or household budget surveys. The aim of this review was to search for studies on the availability of UPF related with mortality and morbidity from noncommunicable diseases or their risk factors. Methods: PRISMA guideline was used. Searches were performed on PubMED, EBSCO, Scopus and Web of Science on December 2019. Search strategy included terms related with exposure (UPF) and outcomes (mortality or morbidity from noncommunicable diseases and their risk factors). Studies were selected based on the title and abstracts. Full texts were screened for eligibility and the snowballing method was used to find other relevant studies. To be based on UPF availability data and its relation with health outcomes were the inclusion criteria. Studies that assessed only food consumption at an individual level and did not present health outcome were excluded. Selection was conducted by two reviewers and a third helped when disagreement occurred. Results: After duplicates removal, 560 records were analyzed. From the 11 eligible studies, 55% were conducted in more than one country. Others were performed in Brazil (27%), Guatemala (9%) and Sweden (9%). Studies were ecological (64%), cross-sectional (27%) and longitudinal (9%). All had representative samples, 45.5% were national samples, and the others were from particular population subgroups. In all studies, the only health outcomes that showed positive association with UPF availability were overweight and obesity prevalence. Conclusions: Studies relating ultra-processed food availability and health outcomes are mainly focused on overweight and obesity. It is thus necessary to further explore the relationship between UPF availability and other health outcomes. Key messages: It is necessary to further research association between ultra-processed food availability and other health outcomes, such as morbidity and mortality from cardiovascular diseases, diabetes or cancer. Purchase lists or household budget surveys are an important source of food availability data and can be used to relate the consumption of ultra-processed foods to health outcomes.